MEDIA PEMBELAJARAN INTERAKTIF: Learning Media;Interactive;Mathematics;Adobe Flash CS6. - Nilawati; Riswan; Oktavia, Lyly (LP2M Universitas Nurdin Hamzah, 2022)
State Elementary School 94/IV is a public education school located in Jambi City, Indonesia. State Elementary School 94/IV Jambi City is an educational institution operated or provided by the government. The learning that has been implemented is based on the Learning Implementation Plan (RPP) and the syllabus that has been implemented according to the K13 guidelines (2013 curriculum) and has 6 classrooms. However, Elementary School 94/IV has not implemented a teaching system using learning videos or other interactive learning media in order to attract students' attention and focus in the teaching-teaching process. With the analysis of these problems, the researchers tried to design an interactive learning media system in the form of animation using Adobe Flash CS6 with the aim of attracting attention, focus and motivation for students' interest in learning Mathematics. With interactive learning media methods students can optimize understanding in learning Mathematics so that the teaching-teaching process becomes effective and efficient.